PROSES PERSIAPAN PROGRAM BUSINESS MATCHING DALAM PAMERAN PLASTICS AND RUBBER INDONESIA 2023 OLEH PT PAMERINDO INDONESIA - Inayah Putri, Nabilah; Setyawan, Heri (Bisnis Event, 2025)
The business matching program is a crucial element in supporting the growth and development of the MICE industry. One of the key roles of this program is to enhance sales by providing a direct meeting platform between business actors and potential consumers. The Plastics and Rubber Indonesia 2023 exhibition by PT Pamerindo Indonesia reflects a focus on the practical application of the business matching program in a specific exhibition. The purpose of this report is to present information on the preparation and implementation process, as well as the challenges and solutions undertaken in the Business Matching program at the Plastics and Rubber Indonesia 2023 exhibition. The research method used is qualitative with a descriptive approach. The results of this study indicate that the preparation process for the Business Matching program at the Plastics and Rubber Indonesia 2023 exhibition went well.   Keywords: Program, Business Matching, MICE, and PT Pamerindo Indonesia